Healthcare changes and the affordable care act : A Physician Call to Action - Powers, James S. (Springer International Publishing : Imprint: Springer, 2015)
Healthcare Changes and the Affordable Care Act: A Physician Call to Action provides guidance, examples, and information on processes and timelines for physicians based on the implementation of The Affordable Care Act (ACA) that was established in 2010. This volume focuses on how geriatricians and other healthcare professionals can be engaged in responding to the roll-out of the ACA in their communities, and through this engagement assume leadership roles in local hospitals, healthcare organizations, and medical societies to advance quality improvement and new models of care for older adults. In-depth chapters provide an update on quality improvement efforts at the state level as well as changes in Medicaid financing and the significant impact this will have for older adults, particularly dual-eligibles. Many elements of the ACA are yet to be rolled out and many healthcare decisions are yet to be made.   Healthcare Changes and the Affordable Care Act: A Physician Call to Action will guide healthcare decision makers and help them to play a leadership role in advancing quality care for older adults in our changing healthcare environment.